KAJIAN DERET FIBONACCI DAN GOLDEN RATIO DALAM PENCIPTAAN LAGU - Harry Mahardika, Putu; Putu Ida Harini, Luh; Eka Nila Kencana, I Putu (Jurnal Ilmiah AdMathEdu, 2012)
In mathematics, beauty can be thought of as a "certain expectation" for a "natural outcome". Mathematical sciences application have appeared in the field of art, particularly music. One example of its application namely Fibonacci sequence and Golden Ratio. This research aims to create two songs with the Fibonacci sequence and Golden Ratio. The first song were created by applying the elements of the Fibonacci 100% while the second song with the implementation of Fibonacci 64%. Then the sense value ratio from both songs are analyzed using the Wilcoxon test with 16 respondents from ISI Denpasar students (Indonesian Art Institute in Denpasar). This research is expected to add knowledge about the mathematics application to the arts, escpecially the art of music.